2018
DOI: 10.7567/jjap.57.06hg01
|View full text |Cite
|
Sign up to set email alerts
|

Elemental depth profiles and plasma etching rates of positive-tone electron beam resists after sequential infiltration synthesis of alumina

Abstract: By scanning transmission electron microscopy and energy dispersive X-ray spectroscopy (STEM–EDS), we investigated the elemental depth profiles of organic electron beam resist films after the sequential infiltration synthesis (SIS) of inorganic alumina. Although a 40-nm-thick poly(methyl methacrylate) (PMMA) film was entirely hybridized with alumina, an uneven distribution was observed near the interface between the substrate and the resist as well as near the resist surface. The uneven distribution was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 27 publications
(43 reference statements)
2
25
0
Order By: Relevance
“…The STEM tomography characterization reveals that in the SIS conditions used in this study, Al 2 O 3 precursors did not penetrate deeply into the particles; we estimate the Al 2 O 3 nanostructure layer thickness to be 240 ± 10 nm. This thickness depends on the precursor diffusion in SIS and can be tuned by varying the exposure time to the metalorganic precursor in the ALD . Additionally, the oxygen plasma only partially etched away the polymer, leading to polymer volume at the center of the particle.…”
Section: Resultsmentioning
confidence: 99%
“…The STEM tomography characterization reveals that in the SIS conditions used in this study, Al 2 O 3 precursors did not penetrate deeply into the particles; we estimate the Al 2 O 3 nanostructure layer thickness to be 240 ± 10 nm. This thickness depends on the precursor diffusion in SIS and can be tuned by varying the exposure time to the metalorganic precursor in the ALD . Additionally, the oxygen plasma only partially etched away the polymer, leading to polymer volume at the center of the particle.…”
Section: Resultsmentioning
confidence: 99%
“…These are by far the most commonly utilized techniques for the dimensional characterization of nanomaterials, requiring simple calibration of the magnification using calibration samples with features in the same dimensional range as the analyzed ones [ 57 ]. Electron microscopy has been widely reported for the morphological characterization of block copolymers nanopatterns or polymeric films treated with SIS of inorganic compounds [ 31 , 35 , 51 , 56 , 58 , 59 , 60 , 61 ]. Electron microscopy is often complemented by energy-dispersive X-ray (EDX) spectroscopy.…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…It is based on the detection of characteristic X-rays produced from the interaction of high-energy electrons with the specimen atoms, allowing the univocal analysis of the elemental composition. This technique has been used for both in-plane and in-depth chemical characterization of the infiltrated polymer [ 31 , 43 , 51 , 59 , 61 , 62 , 63 ].…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…As the film thickness reduces, the influence of the substrate surface becomes non-negligible. In addition, it has been reported that the properties of thermoplastic polymers in thin films are different from those in thick films or bulk materials. Moreover, the inhomogeneity of thin polymer films was suggested in our previous report on the sequential infiltration synthesis of inorganic alumina in a 40-nm-thick poly­(methyl methacrylate) film by the infiltration of the inorganic precursor trimethylammonium and reaction with H 2 O; the synthesized alumina were unevenly distributed near the film surface and film–substrate interface . Therefore, the photoinduced reorientation behavior in thin films is expected to be different from those in thick films; nevertheless, such behavior in sub-100-nm-thick LC polymer films has not been thoroughly studied.…”
Section: Introductionmentioning
confidence: 96%
“…52−54 Moreover, the inhomogeneity of thin polymer films was suggested in our previous report on the sequential infiltration synthesis of inorganic alumina in a 40-nm-thick poly(methyl methacrylate) film by the infiltration of the inorganic precursor trimethylammonium and reaction with H 2 O; the synthesized alumina were unevenly distributed near the film surface and film−substrate interface. 55 Therefore, the photoinduced reorientation behavior in thin films is expected to be different from those in thick films; nevertheless, such behavior in sub-100-nm-thick LC polymer films has not been thoroughly studied. In this report, we study the photoinduced reorientation in sub-100-nm-thick thin films of a nematic LC polymer tethering phenyl benzoate moieties as the side-chain mesogens.…”
Section: ■ Introductionmentioning
confidence: 99%